HISTOLOGICAL AND IMMUNOHISTOCHEMICAL FEATURES OF PROBABLE PROGRESSION OF LIVER FIBROSIS IN PATIENTS WITH CHRONIC VIRAL HEPATITIS B, C AND B + C - Gavryluk, A.O. (World of Medicine and Biology, 2012)
To determine the likely progression of portal-perisinusoidal fibrosis of the liver in patients with HVH B, C and B + C necessarily required identification of activated star-like cells in perisinusoidal spaces of the lobules of the liver and activated fibroblasts in portal tracts. Simultaneous expression of α-SMA activated perisinusoidal star-like cells and activated fibroblasts of portal tracts shows a high probability of development in the near future mixed portal – perisinusoidal liver fibrosis. Later in patients severe portal-perisinusoidal fibrosis is progressing, which can be revealed by staining of liver sections by van Hyzon and by trichromic method of Masson. In immunohistochemical studies was revealed the accumulation of collagen type IV in the portal tracts and also in perisinusoidal spaces of the liver lobules.